Sustainable Innovation: Concepts and Challenges for Tourism Organizations - Hernández, Mercedes; Vargas, Elva Esther; Delgado, Alejandro; Montes, Juan Manuel (Academica Turistica - Tourism and Innovation Journal, 2022)
Tourism companies are looking for new management strategies for helping to preserve their environment and generate positive effects in their social space. Sustainable innovation (si) is the possibility that organizations must introduce changes, not only in products or services but also in their business model, to achieve a balance between economic, social, and environmental factors. The purpose of this article is to recognize the nature and scope of the existing literature in order to discover patterns of interpretation and lines of research, as well as to create a solid starting point for the academic and working community. We decided on a qualitative systematic review of articles identified in a scientific journal specializing in tourism, sustainability, and business management, using the classification contained in the Web of Science and Scopus databases. We filtered documents based on the criteria of relevance, considering the years from 2010 to 2020. This research includes five categories: business models oriented towards sustainable innovation, sustainable innovation: radical or incremental, dynamic capacities for sustainable innovation, role of stakeholders in sustainable innovation, and drivers of sustainable innovation. Keywords: sustainable innovation, tourism organizations, sustainable business model